2016
DOI: 10.7324/japs.2016.60322
|View full text |Cite
|
Sign up to set email alerts
|

Composition, antioxidant and antimicrobial activities of Eleutherococcus senticosus fruit extracts

Abstract: This study was designed to examine the in vitro antioxidant and antimicrobial activities of essential oil and crude methanolic (MeOH) extract of Eleutherococcus senticosus (common name, Siberian ginseng) fruit and its partitioned fractions, including hexane, ethyl acetate (EtOAc), n-butanol (BuOH) and aqueous. 1,1-dephenyl-2-picryl-hydrazyl free radical scavenging and reducing power assay suggest that antioxidant activity of EtOAc and BuOH fractions is due to the reducing ability of the antioxidant against oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…), which is also in agreement with the studies of Shohael et al [21]. According to Jang et al [22] the fruits of E. senticosus collected in Korea have contained the TPC and TFC in the range of 197.9–334.3 mg/g and 41.2–203.7 mg/g.…”
Section: Resultssupporting
confidence: 90%
“…), which is also in agreement with the studies of Shohael et al [21]. According to Jang et al [22] the fruits of E. senticosus collected in Korea have contained the TPC and TFC in the range of 197.9–334.3 mg/g and 41.2–203.7 mg/g.…”
Section: Resultssupporting
confidence: 90%
“…Results obtained by Jang et al (2016) suggest that the fruit of Siberian ginseng may be a good candidate as a source of antioxidant and antimicrobial ingredients -antimicrobial activity was observed against Kocuria rhizophila (MIC = 125 µg/mL), Micrococcus luteus (MIC = 500 µg/mL), and Escherichia coli (MIC = 63 µg/mL). We determined antibacterial effect of Eleutherococcus senticosus on K. рneumonia (10.5 mm).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, other groups of secondary metabolites have also been found to have antioxidant properties (Matkowski 2008;Jang et al 2016). For example, it was revealed that some ginsenosides from P. ginseng protect rabbit pulmonary endothelium tissue from ROS toxicity .…”
Section: Introductionmentioning
confidence: 99%